Juozas Revuckas on development of logical thinking of pupils in teaching geometry - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2023)
Juozas Revuckas (1924–1991) lectured didactics of mathematicsa at Šiauliai Pedagogical Institute (at present – Šiauliai Pedagogical University) for 35 years. He investigated development of logical thinking of pupils in teaching geometry. On this subject, he had published 4 articles and maintained a thesis.